Software change impact analysis with respect to data protection - Sahakyan, Arus (2019)
Software evolves and becomes more complex faster every year. Changes and alterations occur all the time, and new additions often can be contradictory to their previous implementations or send a ripple effect through the system, creating many disturbances in other areas. Software Change Impact Analysis studies the impact that a change can bring to a system, and in this paper, we will discuss such changes with regard to the EU’s General Data Protection Regulation (GDPR).